Ice lab product (blueprint) / Muhammad Syafiq Hanafi Mohd Ali...[et al.] - Mohd Ali, Muhammad Syafiq Hanafi; Awang, Mohamad Asieffiman; Mohd Hisham, Muhammad Hanif; Amiruddin, Mohammad Zahid; Jaffaridin, Muhammad Fadhlin Adam (2017)
Ice Lab is a shop that sells frozen treat which is popsicles. The popsicles are made by our trusted managers and staffs. Our popsicles can be enjoyed by people of all ages as it comes in assorted flavours which are gummy bears, white grapes, kiwi, berries and etc. Diet people will also like our popsicles as we produce detox popsicles too so we have huge target market to attract. In Ice Lab, operational plan is important for the guidelines on how to provide a better product and service to customers. We are located in UiTM Shah Alam as we have made some research and found out that our target market and population are higher at there because the location is strategic than can give the business a better opportunities. We chose to start the business operation on 1 January 2020 because we want to ensure that our business will run smoothly as planned and by the time, we will promote our popsicles and attract the customer's attention. As a new company in this industry, our company will guarantee the satisfaction to our customers that our product is suitable and we will ensure that the price offers are affordable. In addition, Ice Lab will attract the customers to come to our shop by providing good service and environment as well as comfortable place to hang out. As the demands for our product increase, we believe that we can conquer the industry and achieve our vision and mission.